Modern Church Architecture as an Intercultural Space of Aesthetic and Moral Communication - V. V. Barashkov (Концепт: философия, религия, культура, 2020)
The paper analyses the messages modern architecture communicates to audience and to individual. Architects and theologians regard a church as a community place, and raise questions of aesthetic features of church buildings. At the same time, church space is essential to the visitors’ abilities to remember, to compassionate and to concentrate.The article focuses on the concepts of three modern theologians: Thomas Erne, Bert Daelemans and Sigurd Bergmann. According to Erne, churches are becoming a space of self-transcendence; they are open to various social and aesthetic values within the sphere of the infinite. Daelemans formulates three dimensions of a church building — synaesthetic, kerygmatic and eucharistic — and doing so, establishes the notion of theotopy, the nonverbal theology of architecture. Bergmann considers the sacred place as a critical place. In addition, architects seek not only the theological reflection on such spaces, but also on solutions that reveal their transcendental dimension.Church architecture gives an opportunity to express the inexpressible by figurative means, keeping in mind the thoughts of the visitors. A complex religious space, a church is presented to a person and, therefore, can be grasped in a range of ways. So the church space is constructed. Overall, as a space for dialogue and communication, which is not only a religious, but also an aesthetic and moral construct, a temple remains significant despite secularization trends.